Investigating the Relationship between Population and CO2 Emissions from Transportation Systems: An Evidence from Asian Countries - SADHUKHAN, Shubhajit; RATHEE, Chetna (Journal of the Eastern Asia Society for Transportation Studies, 2024)
Transportation sustainability is critical in Asia, given the region's population and economic growth. This research paper investigates the relationship between population and fuel consumption in Asia's ten most populous countries. Using the Granger Causality test, this study examines if a country's population significantly predicts fuel consumption. The findings suggest that no significant relationship exists between the population and fuel consumption, indicating that population growth does not necessarily lead to increased fuel consumption. These results have important implications for policymakers and researchers seeking to understand the factors driving fuel consumption in Asia. To improve transportation sustainability in these countries, there is a need for policies and strategies that focus on reducing transportation emissions and improving energy efficiency. Therefore, there is a need for an integrated approach that considers the development of sustainable transportation systems. This study can inform policymakers and stakeholders in developing sustainable transportation systems.